Proposal of a video-tutorial for the software Sonic Pi - Sedeño-Valdellos, Ignacio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
A tutorial is designed to teach music in Secondary Education, to deal with elements that intervene in the construction of a musical work such as melody, rhythm, harmony, timbre and tempo or dynamics. The proposal aims to be a guide or to trace a different path towards the acquisition of these same curricular contents, through a tutorial of the sound creation software through code, Sonic Pi. Through playful learning, linked to gamification, new forms of learning are promulgated, promoting motivation. A final evaluation tool is designed.